Classical molecular tests using urine samples as a potential screening tool for human papillomavirus detection in human immunodeficiency virus-infected women (2013)
Human papillomavirus (HPV) is the main risk factor associated with the development of cervical cancer (CC); however, there are other factors, such as immunosuppression caused by the human immunodeficiency virus (HIV), that favor progression of the illness.This study was thus aimed at evaluating the functionality of classical PCR-based molecular tests for the generic identification of HPV DNA (GP5-/GP6-, MY09/MY11, and pU1M/2R primers, individually or in combination) using cervical and urine samples from 194 HIV-positive women.Infected samples were tested with type-specific primers for six high-risk types (HPV-16, -18, -31, -33, -45, and -58) and two low-risk types (HPV-6 and -11).HPV infection prevalence rates were 70.1% for the cervical samples and 63.9% for the urine samples.HPV-16 was the most prevalent viral type in the cervical and urine samples, with higher rates of multiple infections than single infections detected in such samples.HPV DNA detection by PCR (mainly with the pU1M/2R primer set) in rine samples was positively associated with abnormal cytological findings (atypical squamous cells of undetermined significance/squamous intraepithelial lesions [ASCUS/SIL]).It was determined that the operative characteristics for detection of cytological abnormalities were similar for cervical and urine samples.This suggested using PCR for the detection of HPV DNA in urine samples as a potential screening strategy for CC prevention in future prevention and control programs along with currently implemented strategies for reducing the impact of the disease, i.e., urine samples are economical, are easy to collect, have wide acceptability among women, and have operative characteristics similar to those of cervical samples.© 2013, American Society for Microbiology.All Rights Reserved.